Hepatocerebral Degeneration or Valproate Toxicity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Six children with refractory seizures and focal neuronal damage who died of liver failure are reported from the Washington University School of Medicine, St Louis, MO.